Interleukin 8 and hepatocyte growth factor in predicting development of severe acute pancreatitis - Anne K. Penttilä; Outi Lindström; Johanna Hästbacka; Krista Kuuliala; Harri Mustonen; Pauli Puolakkainen; Antti Kuuliala; Marko Salmi; Mari Hämäläinen; Eeva Moilanen; Heikki Repo; Leena Kylänpää (Cogent Medicine, 2017)
Objectives: We aimed to study if interleukin (IL) 8 and hepatocyte growth factor (HGF) predict development of severe acute pancreatitis (SAP) among patients without organ dysfunction (OD) at presentation, and if they discriminate transient OD from persistent OD among patients presenting with OD. Methods: From prospectively collected cohort of 176 AP patients and 32 healthy controls, plasma levels of IL-8 and HGF were determined within 5 days after symptom onset using an enzyme-linked immunosorbent assay. Results: AP was severe in 23 patients, of whom 10 did not have clinical signs of OD at presentation. IL-8 and HGF levels increased along with the severity of AP (P < 0.001). In patients without OD at study entry, IL-8 and HGF values predicted the development of SAP with the AUCs of 0.73 (95% CI, 0.56–0.91) and 0.79 (95% CI, 0.66–0.93), respectively. Of all patients, 22 presented with OD, and among them IL-8 predicted persistence of OD with the AUC of 0.88 (95% CI 0.69–1.0). Combining IL-8 and HGF did not improve the models. Conclusions: In AP patients without OD at presentation, circulating levels of IL-8, or HGF, may predict the development of SAP. In patients presenting with OD, IL-8 level may discriminate the patients with transient OD from those with persistent OD.